New insights on trust in business-to-business relationships : a multi-perspective approach - Akrout, Houcine; Raies, Karine; Woodside, Arch G. (Advances in business marketing & purchasing, 2019)
Trust plays a crucial role in all societies, particularly within the Business-to-Business context where inter-firm relationships, impelled by globalization and the extended enterprise, require a much higher degree of trust to succeed. This 26th volume of Advances in Business Marketing and Purchasing examines the value of trust within the B2B context to provide a better understanding of its importance in organizations.New Insights on Trust in Business-to-Business Relationships: A Multi-Perspective Approach applies different theoretical and methodological perspectives to the mechanisms and processes that promote trust between customer and supplier in contexts such as e-commerce, high involvement relationships, industrial service and international cultures. The authors identify the consistencies and distinctions of antecedents, processes, and consequences of trust in various B2B contexts and offer alternative approaches that contribute to a better understanding of the subtleties and multi-faceted nature of trust and trust-related management.The book provides advanced original insights on trust for researchers and practitioners working within Management, Purchasing and B2B Marketing, and offers practical tools to build lasting and successful business relationships.